Kakabakaba ka ba? - De Leon, Encarnacion; De Leon, Manuel; Ilustre, Lorrie; Lacap, Rody.; Jarlego, Ike.; Del Mundo, Clodualdo; Villavicencio, Raquel; De Leon, Mike.; De Leon, Christopher; Concio, Charo Santos-.; Ilagan, Jay.; Andolong, Sandy; et al. (Manila LVN Pictures, 1980)
Two pairs of lovers get caught between dope-trading Japanese and Chinese agents when one of them unsuspectingly smuggles a cassette tape containing opium into the country.
VHS Hi-fi.
Executive producers, Encarnacion de Leon, Manuel de Leon ; original music by Lorrie Ilustre ; cinematography by Rody Lacap ; film editor, Ike Jarlego, Jr. ; screenplay by Clodualdo Del Mundo, Jr., Raquel Villavicencio, Mike de Leon ; directed by Mike de Leon.
Christopher de Leon, Charo Santos, Jay Ilagan, Sandy Andolong, Boboy Garrovillo, Johnny Delgado, Armida Siguion-Reyna.
Keywords: Drug traffic -- Philippines -- Drama; Couples -- Philippines -- Drama; Mafia in motion pictures; Opium trade -- Philippines -- Drama